Eigendom: A Dutch Colonial Legacy in Indonesia's Land Ownership System in Case Number 109 PK/Pdt/2022 - Syifa, Awalia; Maskanah, Ummi (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, Indonesia's land ownership system should have fully adopted the provisions of the 1960 Basic Agrarian Law (Undang-Undang Pokok Agraria or UUPA), which abolished eigendom as a form of property ownership. However, in reality, legal disputes persist regarding former eigendom verponding land, as seen in Case Number 109 PK/Pdt/2022. This case reflects legal issues concerning land rights originating from the colonial system and their implications for legal certainty in land ownership in Indonesia. This study aims to analyze the legal status transformation of eigendom verponding after the enactment of the 1960 UUPA and to examine the legal impact of the Judicial Review (Peninjauan Kembali or PK) decision in Case Number 109 PK/Pdt/2022. This article falls under qualitative library research using a normative legal study methodology. The findings indicate that the legal status of eigendom verponding has been converted according to national agrarian regulations. However, in practice, differences in legal interpretation continue to arise, leading to land ownership disputes. Case 109 PK/Pdt/2022 reaffirms that land title certificates issued under agrarian law provisions hold greater legal recognition than ownership claims based on colonial-era eigendom verponding.